IMPLIKATUR DAN KESANTUNAN POSITIF TUTURAN JOKOWI DALAM TALKSHOW MATA NAJWA DAN IMPLEMENTASINYA SEBAGAI BAHAN AJAR BAHASA INDONESIA DI SMK - N, Zain Syaifudin (Jurnal Penelitian Humaniora, 2013)
The purpose of this research is to (1) set forth a form of speech implicature of Jokowi, President of Indonesia, in the Mata Najwa talkhow, (2) expose the existence of positive politeness strategies iused in the Najwa talkshow, (3) set forth the form of learning materials developed from implicature and positive politeness in the Indonesia language learning, especially in Junior High School. Research method used in analyzing the data is descriptive qualitative method, and the strategies used in this research is embedded research. In addition, the researcher also make use of advanced engineering record and note as data collection techniques. The results of the study indicate the followings: (1) the form of implicature in Jokowi?s speesh contains some mean affects, refusal, convincing, quips, rule, forbidding, threatening, clarification, and complain; (2) the positive politeness strategies used indicate equality through preassumption, as mark solidarity group, fencing, optimistic opinion, banter, involving partners, repeating a por- tion of the speech, praise and humble himself, avoid disagreement, giving the offer, and pay attention to the needs of the partner?s speech; (3) these findings can be implemented on the Indonesian Language course, especially at the 10th grade of Vocational school.